A chair for my mother - Williams, Vera B. (New York : Greenwillow Books, 2007)
A child, her waitress mother, and her grandmother save dimes to buy a comfortable armchair after all their furniture is lost in a fire.
"HarperTrophy"--Spine.
"A Reading Rainbow feature selection"--Back cover.
Art techniques used: Childlike watercolor in vivid hues.
Keywords: Families -- Fiction; Single-parent families -- Fiction; Grandmothers -- Fiction; Saving and investment -- Fiction; Chairs -- Fiction; Fires -- Fiction; Generosity -- Fiction; Waitresses -- fiction